Multi-point momentum interpolation correction on collocated meshes - Zhang, Yaoxin; Jia, Yafei (Journal of computational physics, 2022)
Since the momentum interpolation method was proposed by Rhie and Chow in 1983, it has been widely used in studies of Computational Fluids Dynamics (CFD). The conventional momentum interpolation methods were designed across the edge between two neighboring cells. In this study, an alternative momentum interpolation method, called multi-point momentum interpolation correction (IC) method, is proposed. The proposed IC method is distinguished from the conventional cross-edge momentum interpolation methods by correcting and improving the edge velocity with the interpolated values of its surrounding edges. Examples including analytic, experimental and field cases demonstrated that the proposed IC method is generally capable of improving the convergence process and numerical accuracy.